Populasi Mikroba Rumen, Fermentabilitas, dan Kecernaan Suplementasi Daun Kelor dalam Ransum Sapi Perah secara In Vitro: Microbial Rumen Population, Fermentability, and Digestibility of Moringa Leaf Supplementation in Dairy Cow Ration using In Vitro - Rika Zahera; Junita Purwanti; Dwierra Evvyernie (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2022)
This study aimed to evaluate the microbial rumen population, fermentability, and digestibility of Moringa leaf supplementation in dairy cow ration using in vitro and to determine the optimal level of supplementation. The experiment consist of two steps with the first step was microbiology measurement used a Randomized Block Design with 5 treatments level of Moringa leaf extract (P0= control; P1= 5%, P2 = 10%, P3 =15%, P4 =20%) and the second step was in vitro fermentability and digestibility measurement used Randomized Block Design with 7 treatments level of Moringa leaf in dairy cow ration (R0 = control, R1 = R0 + 2.5% Moringa leaf, R2= R0 +5% Moringa leaf, R3 = R0 + 7.5% Moringa leaf, R4= R0+10% Moringa leaf, R5=R0+12.5% Moringa leaf, R6=R0+15% Moringa leaf) which grouped by rumen fluids. Data analysis used analysis of variance and continued with Duncan’s Multiple Range Test. The measured variable were microbial rumen population (bacteria and protozoa), fermentability (N-NH3, VFA), microbial protein synthesis, dry matter digestibility (DMD), and organic matter digestibility (DMO). The results showed Moringa leaf extract significantly decreased bacterial population (p<0.05), but there was no effect on the protozoa population. Moringa leaf supplementation did not affect N-NH3, DMD, and DMO, but significantly influenced VFA concentration and microbial protein synthesis (p<0.01). The higher Moringa leaf supplementation showed decreasing total VFA concentration, but was still within the normal range for rumen fermentation (102.29-126.69 mM). Moringa leaf supplementation showed a quadratic effect on microbial protein synthesis with an optimal supplementation level of 5%, but decreasing at a level of 7.5% still within in normal range. It can be concluded Moringa leaf can be supplemented up to 7.5% in dairy cow ration. Key words: digestibility, fermentability, in vitro, moringa leaf, dairy cow